Charting a course for incorporating restoration in marine planning - Tundi Agardy; Boze Hancock; Anne Birch; Elizabeth McLeod (Discover Conservation)
Abstract The marine management community is missing critical opportunities to incorporate restoration into coastal planning as well as formal marine spatial planning (MSP) initiatives. Not committing to restoration as decisions are made on how to allocate ocean space and resources means that priority areas for restoration are being ignored, and the potential for using management to restore ecosystem services and improve human well-being may not be met. Large scale restoration, widely acknowledged as needed, is much more difficult in the absence of a systematic framework to remove pressures or practice active reconstruction in key ecologically linked habitats. To address this deficit, we highlight how restoration can be brought into MSP processes across eight waypoints: (1) determining if restoration can be added as a goal of existing MSP; (2) scoping the problems to craft the correct restoration solutions in the planning area; (3) committing to reconciling development with conservation; (4) utilizing MSP frameworks for restoration in a constellation of interlinked sites; (5) doing participatory master planning to set priorities for action; (6) planning with long time horizons and adaptation in mind; (7) building the foundation for long-term financing; and (8) coming to scale. We show how linking restoration planning with MSP has reciprocal benefits: restoration can be done more efficiently and at larger scales when interventions occur across linked habitats, and marine spatial plans can catalyze broader outcomes when degraded areas are restored to their full potential for ecosystem service delivery. Restoration aims to result in healthier ecosystems, greater delivery of ecosystem services, more ‘usable’ space for both humans and nature, and enhanced values—potentially diminishing conflicts and improving well-being in coastal communities.